Genotype-Dependent Difference in 5-HT2C Receptor-Induced Hypolocomotion: Comparison with 5-HT2A Receptor Functional Activity - Darya V. Bazovkina; Elena M. Kondaurova; Vladimir S. Naumenko; Evgeni Ponimaskin (Neural Plasticity)
In the present study behavioral effects of the 5-HT2C serotonin receptor were investigated in different mouse strains. The 5-HT2C receptor agonist MK-212 applied intraperitoneally induced significant dose-dependent reduction of distance traveled in the open field test in CBA/Lac mice. This effect was receptor-specific because it was inhibited by the 5-HT2C receptor antagonist RS102221. To study the role of genotype in 5-HT2C receptor-induced hypolocomotion, locomotor activity of seven inbred mouse strains was measured after MK-212 acute treatment. We found that the 5-HT2C receptor stimulation by MK-212 decreased distance traveled in the open field test in CBA/Lac, C57Bl/6, C3H/He, and ICR mice, whereas it failed to affect locomotor activity in DBA/2J, Asn, and Balb/c mice. We also compared the interstrain differences in functional response to 5-HT2C and 5-HT2A receptors activation measured by the quantification of receptor-mediated head-twitches. These experiments revealed significant positive correlation between 5-HT2C and 5-HT2A receptors functional responses for all investigated mouse strains. Moreover, we found that 5-HT2A receptor activation with DOI did not change locomotor activity in CBA/Lac mice. Taken together, our data indicate the implication of 5-HT2C receptors in regulation of locomotor activity and suggest the shared mechanism for functional responses mediated by 5-HT2C and 5-HT2A receptors.